Good agronomic practices: Varieties capsicum annuum l. And fertilizer dosages influenced and suppressed aphis gossypii population abundance - M. H., Noor Farrah Afiqah; Z., Mohd Rasdi; M. H., Ahmad Khairuman (Asian Journal of Agriculture and Rural Development, 2025)
A field study was conducted on the population abundance of the pest, Aphis gossypii, on several selected Kulai varieties treated with different fertilizer dosages at Universiti Teknologi MARA Melaka Branch Kampus Jasin, from February to November 2021. Aphis gossypii can cause direct harm to crops. The aim of this study was to assess the influence of different chili varieties (Kulai 1033, Kulai 568, and Kulai 461) and fertilizer dosages low, optimum, high, and control on the population of Aphis gossypii, with five replications each, designed using RCBD. The study found that the least presence of Aphis gossypii was detected in treated chili plants of Kulai 568 with a low fertilizer dosage, while the highest was observed in treated chili plants of Kulai 1033 with a high fertilizer dosage for both cropping periods. In conclusion, the presence of Aphis gossypii was most prominent on plants treated with higher fertilizer levels. Additionally, selecting the optimum fertilizer dosage is a key strategy in pest management, as it plays an important role in mitigating the infestation of aphids.